Review of the book "La educación es política" by Jaume Carbonell Sebarroja - Totoricagüena Barandica, Karmele (Avances en Supervisión Educativa, 2019)
LA EDUCACIÓN ES POLÍTICAAuthor: Jaume Carbonell SebarrojaOriginal title: L'educació és políticaTranslated from Catalan: Manuel León Urrutia.Ediciones Octaedro, S.L.Collection: Educational resources /The Journal of EducationFirst edition: January 2019Soft cover: 224 pagesISBN-10: 8417667032ISBN-13: 978-8417667030Author of the review:Karmele Totoricagüena BarandicaEducation Inspector of Euskadi